Ecohydrological change following rewetting of a deep‐drained northern raised bog. Issue 5 (23rd April 2020) - Gaffney, Paul P.J.; Hugron, Sandrine; Jutras, Sylvain; Marcoux, Olivier; Raymond, Sébastien; Rochefort, Line
Abstract: Restoration of degraded peatland ecosystems (by rewetting) is undertaken to bring back key ecosystem services. However, the restoration process can have a range of ecohydrological effects, due to the associated physical and biogeochemical disturbance. In the case of northern peatlands drained by large and deep ditches, the rewetting effects are relatively unknown. The raised bog Grande plée Bleue (1, 500 ha) is one of the largest pristine bogs in the St‐Lawrence lowlands in North America; however, it contained an old (>60 years), 750 m long, 3.5 m deep, and 8 m wide ditch. Rewetting of the area affected by the ditch was carried out by the construction of six dams at 40 cm elevation intervals and felling of all trees (with diameter at breast height >10 cm) within 30 m. Water table was restored to levels similar to intact bog reference sites, only at elevation differences up to 17 cm from the nearest lower dam, while rewetting did not affect pore‐water chemistry. Five to 6 years post‐rewetting, the cover of both pioneer mosses, and late successional mosses ( Sphagnum ) had not changed significantly compared with pre‐rewetting. This may have been due to the presence of dense shrub cover. For more effective ecohydrological restoration, dams should be spaced at smaller elevation intervals (e.g., every 20 cm of elevation or less), to allow recovery of water table along the entire length of the ditch, and vegetation introduction using the moss layer transfer technique may accelerate Sphagnum recruitment, especially in the few first metres from the ditch.